Capital Cost and Profitability in Heavy Machinery Rental Companies for Large Mining (LACCEI, 2024)
Abstract- The purpose of this study is to determine the weighted average cost of capital and profitability in the sample: Zamine Perú S.A.C. - Cajamarca, implementing a quantitative, non-experimental, and longitudinal approach, since it is intended to expose the cost of capital variable by applying the methodologies of the Capital Asset Pricing Model (CAPM) and the Weighted Average Cost of Capital (WACC), and the profitability variable by applying the methodologies of the Economic Value Added (EVA) and the Free Cash Flow (FCF). It was determined that even though this type of company works with a high percentage of debt, which affects the reduction of profitability, it also considerably reduces the cost of capital, so it remains a conservative and profitable company.